Synthesis and self-assembly of cytidine- and guanosine-based copolymers. Issue 35 (11th August 2022) - Chea, Sany; Schade, Kristin; Reinicke, Stefan; Bleul, Regina; Rosencrantz, Ruben R.
Abstract : The base pairing property and the "melting" behavior of oligonucleotides can take advantage to develop new smart thermoresponsive and programmable materials. Abstract : The base pairing property and the "melting" behavior of oligonucleotides can take advantage to develop new smart thermoresponsive and programmable materials. Complementary cytidine- (C) and guanosine- (G) based monomers were blockcopolymerized using RAFT polymerization technique with poly-( N -(2-hydroxypropyl) methacrylamide) (pHPMA) as the hydrophilic macro chain transfer agent (macro-CTA). C–C, G–G and C–G hydrogen bond interactions of blockcopolymers with respectively C and G moieties have been investigated using SEM, DLS and UV-Vis. Mixing and heating both complementary copolymers resulted in reforming new aggregates. Due to the ribose moiety of the isolated nucleoside-bearing blockcopolymers, the polarity is increased for better solubility. Self-assembly investigations of these bioinspired compounds are the crucial basis for the development of potential future drug delivery systems.